Rancang Bangun Sistem Pelayanan Jasa Bubut Berbasis Web Pada CV. Sukses Abadi Jaya Tangerang - Ari Febrianto; Popon Handayani (Paradigma, 2019)
The development of the world's auto industry that is very significant, promoted demand for spare parts and fitting services. In improving the performance of a company can take advantage of science and information technology. To date CV. The lasting success of this Triumphant doing marketing and promotion with the conventional way i.e. waiting for buyers or service users come in and out of the mouth to the mouth, it needs a breakthrough promotions and delivery information more effectively and efficiently. In the system of bookkeeping results in sales of products and services still use the system manually, that is only written in the great book. In this case the company workshop lathe takes innovation to change the bookkeeping systems still using manual systems into a computerized system for fast and accurate results. Based on the foregoing, required a data processing information system design and means of promotion in the workshop, then writers interested in creating a system of web-based services lathe using the programming language PHP and MySQL with the waterfall method for CV. Successful Perennial Jaya so that later the party workshop will be able to easily do the promotion and inputting data